The BecA-ILRI African Swine Fever Project - International Livestock Research Institute (International Livestock Research Institute, 2013)
African Swine Fever Epidemiology: A project partnership with AusAID, CSIRO, and the BecA-ILRI Hub. African Swine Fever (ASF) is a devastating emerging disease of pigs that is present in more than 20 countries in Africa. ASF is highly contagious and causes almost 100% mortality in pig herds. Although ASF does not cause infection in people, it impacts on the livelihoods of farmers, and others who trade pigs and pork, through loss of income and food. This project led by the BecA-ILRI Hub in collaboration with CSIRO and funded by AusAID enables an interdisciplinary team of scientists, working with national veterinary officers and ministry staff in Uganda and Kenya, to obtain an in-depth understanding of: - the prevalence and genetic diversity of the virus, - socio-economic impact, and- modes of transmission and spread.